Anti-Erythropoietin Antibody Associated Pure Red Cell Aplasia Resolved after Liver Transplantation. (9th July 2015) - Hung, Annie K.; Guy, Jennifer; Behler, Caroline M.; Lee, Eugene E.
Abstract : Patients undergoing antiviral therapy for chronic hepatitis C often develop anemia secondary to ribavirin and interferon. Recombinant erythropoietin has been used to improve anemia associated with antiviral therapy and to minimize dose reductions, which are associated with decreased rates of sustained virologic response. A rare potential side effect of recombinant erythropoietin is anti-erythropoietin antibody associated pure red cell aplasia. In chronic kidney disease patients with this entity, there have been good outcomes associated with renal transplant and subsequent immunosuppression. In this case, a chronic liver disease patient developed anti-erythropoietin associated pure red cell aplasia and recovered after liver transplantation and immunosuppression. It is unclear whether it is the transplanted organ, the subsequent immunosuppression, or the combination that contributed to the response. In conclusion, anti-erythropoietin associated pure red cell aplasia is a serious complication of erythropoietin therapy, but this entity should not be considered a contraindication for solid organ transplantation.